EWOM, Kepercayaan, Citra Merek Terhadap Niat Pembelian Ulang pada Poliklinik Penyakit dalam di RS ABC Jakarta - Herisa Anjani; Endang Ruswanti; Ratna Indrawati (Syntax Corporation Indonesia, 2022)
Managing the hospital business aspect has become a natural consequence of the era of globalization. The results of a preliminary survey of repurchase intentions at ABC Hospital Jakarta, 30% said they would return to this hospital if they wanted to do a re-examination. Repurchase intention in hospital services is the tendency of customers to take advantage of hospital services again in the future. This study uses a quantitative method with a covariant-based Structural Equation Model (SEM) causal research design, namely AMOS. This study used a sample of 300 hair calculations for outpatients in internal medicine polyclinics. Research results: E-WoM has a significant positive effect on repurchase intentions through patient trust based on the results of measuring CR values ​​using SEM with the help of the Sobel test. Based on the results of the study, the implications of this study indicate the magnitude of the influence of E-WOM and brand image through patient trust which can increase repurchase intentions, marked by changes in the hospital tariff system and relationship marketing in utilizing repurchase intentions